Recognition of Ijarah (Capital Rent) Income from Business Using the Rahn (Pawn) Agreement : JEL Classification: G21, M41, Z12, G28, K22 - Nursakinah Nursakinah; Sahabuddin Sahabuddin; Winarti Winarti (Generasi Sains Indonesia, 2026)
This study aims to analyze the recognition of ijarah income derived from rahn contracts within a Sharia-compliant financial institution. A qualitative case study approach was employed, utilizing observations, in-depth interviews, and documentation to examine accounting practices at PT Pegadaian Daya Branch. The findings indicate that ijarah income is recognized based on the accrual principle at the point when custodial services are initiated, supported by real-time transaction recording systems. The study also reveals a clear separation between financing and service components, ensuring compliance with Sharia principles. Additionally, ijarah rates are determined based on collateral value and service duration, while financial reporting adopt.s a standardized and net presentation approach. The novelty of this research lies in its micro-level analysis of how Sharia accounting standards are operationalized in practice, particularly in hybrid rahn–ijarah transactions. The study contributes to the literature by bridging the gap between theoretical frameworks and real-world implementation. The findings provide practical implications for improving transparency, consistency, and compliance in Islamic financial reporting, as well as theoretical insights into the integration of accrual accounting and Sharia principles within institutional systems.